2002
DOI: 10.1128/jb.184.1.177-182.2002
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Integrative Elements of Rhizobiophage 16-3 Can Integrate into Proline tRNA (CGG) Genes in Different Bacterial Genera

Abstract: The integrase protein of the Rhizobium meliloti 41 phage 16-3 has been classified as a member of the Int family of tyrosine recombinases. The site-specific recombination system of the phage belongs to the group in which the target site of integration (attB) is within a tRNA gene. Since tRNA genes are conserved, we expected that the target sequence of the site-specific recombination system of the 16-3 phage could occur in other species and integration could take place if the required putative host factors were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…Our results confirm, from a statistical perspective, many earlier observations in prokaryotes (Reiter et al, 1989;Parreira and Gyles, 2003;van Aartsen, 2008). This previous work has revealed that tRNA loci are not only central components in translation, but also commonly serve as insertion sites for mobile elements in bacteria because there is an attB (bacterial attachment site) within some tRNA genes such as Arg and Pro (Reiter et al, 1989;Semsey et al, 2002), and therefore, the presence of these tRNA genes gives rise to variable genomic regions and the observed divergence of Prochlorococcus genomes.…”
Section: Trna As An Insertion Hotspotsupporting
confidence: 79%
“…Our results confirm, from a statistical perspective, many earlier observations in prokaryotes (Reiter et al, 1989;Parreira and Gyles, 2003;van Aartsen, 2008). This previous work has revealed that tRNA loci are not only central components in translation, but also commonly serve as insertion sites for mobile elements in bacteria because there is an attB (bacterial attachment site) within some tRNA genes such as Arg and Pro (Reiter et al, 1989;Semsey et al, 2002), and therefore, the presence of these tRNA genes gives rise to variable genomic regions and the observed divergence of Prochlorococcus genomes.…”
Section: Trna As An Insertion Hotspotsupporting
confidence: 79%
“…4A). tRNA genes often serve as target sequences for sitespecific integration of temperate bacteriophages, plasmids, and pathogenicity islands (27,63). Immediately upstream of the proline tRNA (UGG) gene on the B. thailandensis chromosome was a divergently transcribed gene designated orfB (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…X70328). This may suggest a different (4,12,34). In such cases, a phage-or plasmid-encoded site-specific recombinase or integrase mediates integrative recombination.…”
Section: Discussionmentioning
confidence: 99%